Kewirausahaan Dikalangan Gen Z: Suatu Kajian - Siregar, Ilham Jaya Kusuma; Amanda, Tasya; Syahputra, Heru (Jurnal Ilmiah Universitas Batanghari Jambi, 2025)
This research examines the dynamics of entrepreneurship among Generation Z, focusing on business trends such as thrifting, food and beverages, and the development of tourist spots. Generation Z is interested in entrepreneurship due to awareness of environmental issues, sustainability, and the desire to create unique experiences. Thrifting businesses are popular because they offer quality items at affordable prices and support a sustainable lifestyle. In the food and beverage sector, Gen Z shows creativity through product innovation, while the development of Instagrammable tourist spots has also become a trend. The research method used is a mixed-methods approach, combining in-depth interviews and surveys. The results indicate that Gen Z leverages technology and social media to develop their businesses, facing challenges such as lack of experience, but remaining adaptive and innovative. Support from the government and various stakeholders is crucial to creating a conducive entrepreneurial ecosystem. With high creativity and enthusiasm, Gen Z has the potential to become the main drivers of entrepreneurship in the future.